Endocrinology of parturition - Sunil K Kota (Indian Journal of Endocrinology and Metabolism, 2013)
The myometrium must remain relatively quiescent during pregnancy to accommodate growth and development of the feto-placental unit, and then must transform into a highly coordinated, strongly contracting organ at the time of labour for successful expulsion of the new born. The control of timing of labour is complex involving interactions between mother, fetus and the placenta. The timely onset of labour and delivery is an important determinant of perinatal outcome. Both preterm birth (delivery before 37 week of gestation) and post term pregnancy (pregnancy continuing beyond 42 weeks) are both associated with a significant increase in perinatal morbidity and mortality. There are multiple paracrine/autocrine events, fetal hormonal changes and overlapping maternal/fetal control mechanisms for the triggering of parturition in women. Our current article reviews the mechanisms for uterine distension and reduced contractions during pregnancy and the parturition cascade responsible for the timely and spontaneous onset of labour at term. It also discusses the mechanisms of preterm labour and post term pregnancy and the clinical implications thereof.